Estudio de prefactibilidad para la instalación de una planta procesadora de snacks horneados de papa nativa (Solanum tuberosum) - Baldeon Sifuentes, Giancarlo (2021)
The company SNACKS ANDINOS S.R.L. constituted in 2020 presents the project located in south of Lima at kilometer 37.5 of the Panamericana Sur in the district of Lurín. Its main economic activity is represented by ISIC 15499 - ELABORATION OF OTHER FOOD PRODUCTS and has 18 employees among operators and administrative staff. The present project is an alternative in response to the growing demand of healthy products within the category of snacks being its target market all people who have as goal a healthy lifestyle and have a medium - high purchasing power. In addition, the selected business model is the Business-to-Consumer (B2C) and the selected strategy is product differentiation because of the added value focused on replacing the traditional frying process with one of baking. The distribution of the product will be through two channels: the first, with 10% of the volume to be sold will be through the most popular fairs in Lima. And the second, with 90% of the volume to be sold will be through the modern channel; mainly in Tottus, Plaza Vea, Metro, Wong, Vivanda, Tambo and Listo. In addition, the promotion of the product will be under the modality Below The Line (BTL) which is a non-traditional type of advertising and can reach the target market using advertising resources such as promotions through social networks as Facebook and Instagram. Financially, the project is viable, generating a VANE of 509 007 soles and a TIRE of 38.74%, as well as a VANF of 519 118 soles and a TIRF of 54.59%. The critical variables of the project, according to sensitivity analysis, are the volume of sales and the price of native potatoes. Socially, the project generates S /. 8,46 for S/ 1,00 invested and benefits 2 920 328 people, representing 27,6% of Metropolitan Lima in Socioeconomic Levels A and B older than 18 years old.